(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
During 2022-2025, 120 people aged 10 to 18 years were examined and treated in children with deformities of the occlusal surface of the dentition and 35 in healthy children. Malocclusion of the dentition in children - violations of the central symmetry of teeth were observed in 12 children (10%), infraocclusion in 24 people (20%), supraocclusion in 18 people (15%) and secondary toothlessness in 20 children (16.67%). The prevalence of dental caries in children aged 10-18 years averaged 68.7%. The increase in the physiological height of the face was due to the highest temperature in boys and girls aged 14-18 years. The effectiveness of the treatment of children with deformities of the occlusal surface of the dentition, which we recommended, was higher compared to traditional treatment, the effectiveness of treatment was 93.4%.